Hall effect in a GdBa2Cu3O7-δ/La0.75 Sr0.25MnO3 perovskite bilayer - Haberkorn, N.; Bridoux, G.; Osquiguil, E.; Nieva, G.; Guimpel, J.; Haberkorn, Néstor; Guimpel, Julio; Nieva, Gladys (Elsevier, 2007)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina